(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
The ability of bacteria to release enzymes into the environment is widely recognized. Proteases are among the several extracellular enzymes that Bacillus species. which is industrially significant produce. The aim of this work is to identify, characterize and isolate protease producing bacteria from environmental sample. The experiment’s required chemicals, reagents, and culture media include nutrients agar, skimmed milk agar, and gram staining (crystal violet, gram iodine, alcohol, safranin) and biochemical reagent. Samples of soil were taken from the rhizosphere of aloe vera. In sterile containers, 10–15 g of soil was gathered at a depth of 5–10 cm, and they were refrigerated before being brought to the lab. Protease-producing bacteria with a variety of proteolytic activity and biochemical characteristics were found to be abundant in aloe vera soil. It may be possible to future optimize protease activity and clarify their structures, which will aid in the discovery of novel proteases.